A revision of Northern Vietnamese species of the ant genus Pheidole (Insecta: Hymenoptera: Formicidae: Myrmicinae) - Eguchi, Katsuyuki (Zootaxa, 2008)
Northern Vietnamese species of the ant genus Pheidole (Myrmicinae: Pheidolini) were revised, and 31 species including six new species were recognized: capellinii Emery, colpigaleata Eguchi, dugasi Forel, elongicephala sp.n., fervens F. Smith, fervida F. Smith, fortis Eguchi, foveolata Eguchi, gatesi (Wheeler), hongkongensis Wheeler, indosinensis Wheeler stat.n., laevicolor Eguchi, laevithorax sp.n., magna Eguchi, megacephala (Fabricius), noda F. Smith, ochracea sp.n., parva Mayr, pieli Santschi, plagiaria F. Smith, planifrons Santschi, rabo Forel, rugithorax sp.n., smythiesii Forel, taipoana Wheeler, tjibodana Forel, tumida sp.n., vieti sp.n., vulgaris Eguchi, yeensis Forel, zoceana Santschi. The following cases of synonymy were resolved: Myrmica agilis F. Smith as a junior synonym of Pheidole megacephala; Pheidole rhombinoda var. stella Forel, P. rhombinoda var. formosensis Forel, P. rhombinoda var. taprobanae Forel, and P. nodus var. flebilis Santschi as junior synonyms of P. noda; Pheidole peguensis r. yomensis as a junior synonym of P. plagiaria; and Pheidole smythiesii var. bengalensis Forel and P. bhavanae Bingham as junior synonyms of P. smythiesii. The lectotype was designated for the following species: Pheidole dugasi, P. rhombinoda var. stella, P. peguensis r. yomensis and P. sulcaticeps r. yeensis. A key to N. Vietnamese species of Pheidole based on the worker caste is given.